Ensaios de avaliação de compatibilidade de driver de LED de dupla função para operação VLC com especificação IEEE 802.15.7 - Colvero, Gabriel Dacanal (2023)
With the widespread use of commercial wireless communication networks such as Wi-Fi and Bluetooth, coupled with the increasing demand for new communications, especially driven by the concepts of the Internet of Things (IoT), there is a clear observation of the spectrum saturation in the available radio frequency (RF) spectrum. In this context, new communication technologies, such as Visible Light Communication (VLC), have garnered significant interest in the industry. VLC utilizes visible light for wireless data transmission by leveraging existing LED luminaires, provided that modifications are made to their electronic control circuits. This document describes the development of tests to evaluate compatibility, following the parameters established by the IEEE 802.15.7 standard, for a dual-function driver for VLC, intended for use in commercial LED luminaires. The circuit used during the tests was designed to modulate the intensity of light emitted by LED devices without compromising their primary function of illuminating the surroundings. Initially, it was validated through simulations, and subsequently, practical tests were conducted using real LED loads, providing relevant data on its applicability with different types of LED luminaires available in the market. The accordance of the physical layer network with the IEEE 802.15.7 standard was tested to ensure better interoperability of the circuit with other visible light communication systems following the same standard. With a minimum transmission rate of 19.2 Mb/s set as one of the objectives for development, the circuit enables efficient transfer of a wide range of files. Furthermore, techniques and test procedures were proposed and employed to generate high-rate communication signals, starting with the use of a periodic signal generator. For circuit validation, real signals in the form of data packets originating from the Ethernet network communication protocol were used, partially representing the standardization defined by the IEEE 802.15.7 PHY II physical layer and demonstrating more realistic results closer to commercial implementation. The successful experimentation of the dual-function driver circuit tested in this work, along with various commercial LED loads, demonstrates the technical feasibility of using VLC as a practical and effective alternative for data communication through lighting systems employed in different sectors. As a contribution to the advancements of VLC, this work provides a solid theoretical and experimental foundation for this emerging technology, assisting in its ongoing development to enhance efficiency and market adoption of new VLC system proposals in various scenarios. Additionally, the need for conducting future research to overcome the bandwidth limitations of mid-power and high-power LED loads, widely utilized in the lighting industry, was also evaluated.